Aminophosphinates against Helicobacter pylori ureolysis-Biochemical and whole-cell inhibition characteristics. - Katarzyna Macegoniuk; Ewa Grela; Monika Biernat; Mateusz Psurski; Grażyna Gościniak; Anna Dziełak; Artur Mucha; Joanna Wietrzyk; Łukasz Berlicki; Agnieszka Grabowiecka (PLoS ONE)
Urease is an important virulence factor from Helicobacter pylori that enables bacterial colonization of human gastric mucosa. Specific inhibition of urease activity can be regarded as a promising adjuvant strategy for eradication of this pathogen. A group of organophosphorus inhibitors of urease, namely, aminophosphinic acid and aminophosphonic acid derivatives, were evaluated in vitro against H. pylori urease. The kinetic characteristics of recombinant enzyme activity demonstrated a competitive reversible mode of inhibition with Ki values ranging from 0.294 to 878 μM. N-n-Hexylaminomethyl-P-aminomethylphosphinic acid and N-methylaminomethyl-P-hydroxymethylphosphinic acid were the most effective inhibitors (Ki = 0.294 μM and 1.032 μM, respectively, compared to Ki = 23 μM for the established urease inhibitor acetohydroxamic acid). The biological relevance of the inhibitors was verified in vitro against a ureolytically active Escherichia coli Rosetta host that expressed H. pylori urease and against a reference strain, H. pylori J99 (CagA+/VacA+). The majority of the studied compounds exhibited urease-inhibiting activity in these whole-cell systems. Bis(N-methylaminomethyl)phosphinic acid was found to be the most effective inhibitor in the susceptibility profile studies of H. pylori J99. The cytotoxicity of nine structurally varied inhibitors was evaluated against four normal human cell lines and was found to be negligible.